Standardized Passiflora incarnata L. Extract Reverts the Analgesia Induced by Alcohol Withdrawal in Rats. (1st June 2017) - Schunck, Rebeca Vargas Antunes; Macedo, Isabel Cristina; Laste, Gabriela; de Souza, Andressa; Valle, Marina Tuerlinckx Costa; Salomón, Janaína L.O.; Nunes, Ellen Almeida; Campos, Andreia Cristina Wildner; Gnoatto, Simone Cristina Baggio; Bergold, Ana Maria; Konrath, Eduardo L.; Dallegrave, Eliane; et al.
Abstract : Passiflora incarnata L. (Passifloraceae) has been traditionally used for treatment of anxiety, insomnia, drug addiction, mild infections, and pain. The aim of this study was to investigate the effect of a commercial extract of P. incarnata in the analgesia induced by alcohol withdrawal syndrome in rats. In addition, brain‐derived neurotrophic factor and interleukin‐10 levels were evaluated in prefrontal cortex, brainstem, and hippocampus. Male adult rats received by oral gavage: (1: water group) water for 19 days, 1 day interval and water (8 days); (2: P. incarnata group) water for 19 days, 1 day interval and P. incarnata 200 mg/kg (8 days); (3: alcohol withdrawal group) alcohol for 19 days, 1 day interval and water (8 days); and (4: P. incarnata in alcohol withdrawal) alcohol for 19 days, 1 day interval and P. incarnata 200 mg/kg (8 days). The tail‐flick and hot plate tests were used as nociceptive response measures. Confirming previous study of our group, it was showed that alcohol‐treated groups presented an increase in the nociceptive thresholds after alcohol withdrawal, which was reverted by P. incarnata, measured by the hot plate test. Besides, alcohol treatment increased brain‐derived neurotrophic factor and interleukin‐10 levels in prefrontal cortex, which was not reverted by P. incarnata . Considering these results, the P. incarnata treatment might be a potential therapy in the alcohol withdrawal syndrome. Copyright © 2017 John Wiley & Sons, Ltd.